The Impact of the 1994 Federal Assault Weapon Ban on Gun Violence Outcomes: An Assessment of Multiple Outcome Measures and Some Lessons for Policy Evaluation - Koper, Christopher S. (Journal of quantitative criminology, 2001)
The Federal Violent Crime Control and Law Enforcement Act of 1994 bans a group of military-style semiautomatic firearms (i.e., assault weapons) and ammunition magazines capable of holding more than 10 rounds. Ban advocates argue that these weapons are particularly dangerous because they facilitate the rapid firing of high numbers of shots. Though the banned guns and magazines were used in only a modest fraction of gun crimes before the law, it was hypothesized that a decrease in their use might reduce gunshot victimizations, particularly those involving multiple wounds and/or victims. In response to a Congressional mandate for an impact assessment of the law, this study utilized national and local data sources and a variety of analytical techniques to examine the ban's short-term impact on gun violence. The ban may have contributed to a reduction in gun homicides, but a statistical power analysis of our model indicated that any likely impact from the ban will be very difficult to detect statistically for several more years. We found no evidence of reductions in multiple-victim gun homicides or multiple-gunshot wound victimizations. The findings should be treated cautiously due to the methodological difficulties of making a short-term assessment of the ban and because the ban's long-term effects could differ from the short-term impacts revealed by this study.